2010
DOI: 10.3944/aott.2010.2329
|View full text |Cite
|
Sign up to set email alerts
|

Coracoclavicular ligament repair and screw fixation in acromioclavicular dislocations

Abstract: With ease of application, low complication rate, and low rate of acromioclavicular joint arthrosis, the modified Bosworth technique is an effective surgical method in providing satisfactory shoulder function in acromioclavicular dislocations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 28 publications
3
40
0
Order By: Relevance
“…A re-displacement rate of 9-11 % (maximum upto 35% with vertical screw fixation) has been reported with coraco-clavicular fixation and about 5% after AC fixation. [11] In a study by Wei-Ching Lin, a 4.5 mm diameter of cancellous screw with supplementary techniques provided sufficient stability during the recovery period. The main advantage of this technique was its technical simplicity as compared with other techniques and the outcomes were largely similar.…”
Section: Discussionmentioning
confidence: 99%
“…A re-displacement rate of 9-11 % (maximum upto 35% with vertical screw fixation) has been reported with coraco-clavicular fixation and about 5% after AC fixation. [11] In a study by Wei-Ching Lin, a 4.5 mm diameter of cancellous screw with supplementary techniques provided sufficient stability during the recovery period. The main advantage of this technique was its technical simplicity as compared with other techniques and the outcomes were largely similar.…”
Section: Discussionmentioning
confidence: 99%
“…In the current survey because we didn’t use the screw alone, there were no re-dislocations reported, but there was a case of screw fracture as described earlier. Esenyel et al in 2010 treated 32 patients with different ACJ dislocation types (3-6, 28) by coracoclavicular ligament reconstruction and coracoclavicular fixation. They used cancellous screws for 30 patients and cortical screws for the other 2; these 2 patients had screw cut-outs which led to a re-dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…No degenerative changes were seen in the patients and all patients had painless range of motion. Finally, these researchers reported that due to the great results and limited complications and also due to the low incidence of arthritis, this method was appropriate for the treatment of ACJ dislocation and restoration of normal shoulder function (28). Bektaser et al reported an 8.8% re-dislocation rate in patients treated by the Bosworth technique (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been successful in treating acromioclavicular joint dislocations and distal clavicle fractures with good clinical results, there are still several complications such as infection, clavicular stress fracture, acromion fracture, and hook or screw cutout6-8. Screws and in combination with ligament reconstruction were recommended in treatment of acute complete acromioclavicular joint dislocation, and potential complications of this technique include suture cutout9-11. Other surgical techniques to stabilize the lateral clavicle and acromioclavicular joint include reconstruction of the coracoclavicular ligament by using a variety of suture materials or using autograft or allograft tissues12.…”
Section: Discussionmentioning
confidence: 99%